High-resolution X-ray phase-contrast tomography of human placenta with different wavefront markers - Sara Savatović; Davis Laundon; Fabio De Marco; Mirko Riedel; Jörg U. Hammel; Madleen Busse; Murielle Salomé; Lorella Pascolo; Irene Zanette; Rohan M. Lewis; Julia Herzen; Pierre Thibault (Scientific Reports)
Abstract Phase-contrast micro-tomography ( $$\upmu$$ CT) with synchrotron radiation can aid in the differentiation of subtle density variations in weakly absorbing soft tissue specimens. Modulation-based imaging (MBI) extracts phase information from the distortion of reference patterns, generated by periodic or randomly structured wavefront markers (e.g., gratings or sandpaper). The two approaches have already found application for the virtual inspection of biological samples. Here, we perform high-resolution $$\upmu$$ CT scans of an unstained human placenta specimen, using MBI with both a 2D grating and sandpaper as modulators, as well as conventional propagation-based imaging (PBI). The 3D virtual representation of placenta offers a valuable tool for analysing its intricate branching villous network and vascular structure, providing new insights into its complex architecture. Within this study, we assess reconstruction quality achieved with all three evaluated phase-contrast methods. Both MBI datasets are processed with the Unified Modulated Pattern Analysis (UMPA) model, a pattern-matching algorithm. In order to evaluate the benefits and suitability of MBI for virtual histology, we discuss how the complexities of the technique influence image quality and correlate the obtained volumes to 2D techniques, such as conventional histology and X-ray fluorescence (XRF) elemental maps.